2003
DOI: 10.1177/153537020322800204
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hyperglycemia Leads to Gender-Dependent Deficits in Learning and Memory in Offspring

Abstract: Pregnancy in the diabetic woman has long been associated with an increased risk of congenital malformation in the offspring. However, little is known about the effects of maternal diabetes on development of the central nervous system. To begin to gain an understanding of this problem, diabetes was induced in adult female Sprague-Dawley rats by injection with streptozotocin. Only animals with serum glucose levels greater than 200 mg/dl were used. Diabetic and control females were bred, and all newborn pups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…We also noted an apparent increase in preference for novel location in the object-place paradigm without significant effects in object recognition memory. Previous studies have noted impairments in learning and memory in some paradigms, including the Lashley III maze and inhibitory avoidance paradigm in the offspring of dams diabetic for the entire pregnancy (Kinney et al, 2003). Interestingly, these effects were more pronounced in females.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We also noted an apparent increase in preference for novel location in the object-place paradigm without significant effects in object recognition memory. Previous studies have noted impairments in learning and memory in some paradigms, including the Lashley III maze and inhibitory avoidance paradigm in the offspring of dams diabetic for the entire pregnancy (Kinney et al, 2003). Interestingly, these effects were more pronounced in females.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have noted increased anxiety-like behavior (Ramanathan et al, 2000) and no change in behavior on the elevated plus maze (Kinney et al, 2003) in the offspring of diabetic dams. However, in these previous studies, the dams were rendered diabetic before breeding.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Animal models of experimentally induced hyperglycemia are helpful for specifi cally studying the long-range eff ects of maternal hyperglycemia on off spring. Among the models used in animals for hyperglycemia induction during pregnancy, STZ administration prior to pregnancy ( Eriksson et al, 1982 ;Caluwaerts et al, 2003 ;Kinney et al, 2003 ), during pregnancy ( Oh et al, 1991 ;Gelardi et al, 1990 Introduction ▼ Diabetic pregnancy causes reproductive abnormalities that enhance spontaneous abortion, congenital anomalies, and neonatal morbidity and mortality ( Van Assche et al, 1998 ; Eriksson et al, 2003 ). The high rate of birth defects associated with diabetic pregnancy is a signifi cant public health problem that results in congenital malformations in up to 10 % of newborn babies.…”
Section: Maternal-fetal Outcome Lipid Profi Le and Oxidative Stress mentioning
confidence: 99%
“…Studies which directly investigated whether intra-uterine exposure to hyperglycemia and hyperinsulinemia were associated to altered anxiety levels showed confounding results. While some of them report no differences in anxiety levels among rats born from GD dams when diabetes was induced before pregnancy (Kinney et al 2003, Ramanathan et al 2000, one study reported decreased anxiety levels in the offspring when STZ was administered during mid pregnancy (Chandna et al 2015), a condition which more closely resembles the time course of GD development in humans.…”
Section: Mood Disordersmentioning
confidence: 99%